ANXIETY OF BETTINA DANIELS IN DANIELLE STEEL'S NOVEL LOVING (1980): A PSYCHOANALYTIC APPROACH - UTAMI, GLASSINEA NURUL (2010)
The object of the research is the novel entitled Loving by Danielle Steel. The study gives focus on anxiety of Bettina Daniels in Danielle Steel's Loving. The aims of the study are: 1) To analyze the novel based on the structural elements of the novel, 2) To analyze the anxiety of the major character based on the psychoanalytic perspective. The analysis uses descriptive qualitative by describing the structural elements and psychoanalytic analysis. The approach is psychoanalytic theory. The primary source of criticism toward the novel is used for further analysis. The data collecting technique is library research. The data analysis uses descriptive technique and content analysis. The result of the study shows that: Firstly, the structural elements of the novel consist of character and characterization, setting, plot, point of view, style and theme are related to each other and form the unity into good quality of a novel. Secondly, the Psychoanalytic analysis shows that the suffering anxiety is not enough if people only grieve the conflict, but she must fight the conflict by working and praying.